Armed Conflict, Gender, and Schooling - Buvinić, Mayra (Oxford University Press on behalf of the World Bank, 2015)
The impact of armed conflict on gender differentials in schooling appears to be highly context-specific, as the review of the literature and the findings from the three studies in this symposium reveal. In some settings boys' schooling is more negatively affected than that of girls. In others, the reverse is the case. Effects are largely shaped by events surrounding a conflict, pre-war gender differences in educational attainments, and education and labor market opportunities in the absence of war. Rigorous evaluations of post-conflict policies and aid projects can provide useful information to address educational needs and gender differentials in these environments.